2011
DOI: 10.1159/000333557
|View full text |Cite
|
Sign up to set email alerts
|

Review of Postpartum Contraceptive Practices at Chiang Mai University Hospital: Implications for Improving Quality of Service

Abstract: Objective: To evaluate the acceptance rate and patterns of contraceptive use among postpartum women. Subjects and Methods:The records of 1,009 postpartum women attending the Family Planning Clinic at Chiang Mai University Hospital, Thailand, during January to December 2009 were reviewed.Results: Mean age was 28.2 ± 5.7 years (range 15-48). Almost all 920 women (91.2%) practiced breastfeeding. The acceptance rate of contraception was 97.6%. The types of contraceptive used were: depot medroxyprogesterone acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…The potential explanation could be attributed to the difference in socioeconomic status, sociocultural values, norms, religious beliefs, and study setting and area. Similarly, our result is substantially lower as compared with the review conducted at Chiang Mai University Hospital, Thailand (97.6%) [53], and Rwanda (51.1%) [52]. This divergence might be due to the differences in health policy of the respective countries, difference in culture and study design, accessibility of contraceptives, male involvement, and study participant level of understanding towards the health benefits of using a postpartum contraceptive.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The potential explanation could be attributed to the difference in socioeconomic status, sociocultural values, norms, religious beliefs, and study setting and area. Similarly, our result is substantially lower as compared with the review conducted at Chiang Mai University Hospital, Thailand (97.6%) [53], and Rwanda (51.1%) [52]. This divergence might be due to the differences in health policy of the respective countries, difference in culture and study design, accessibility of contraceptives, male involvement, and study participant level of understanding towards the health benefits of using a postpartum contraceptive.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, 12 primary articles were excluded because of the study population and outcome of interest. Among these, eight of the studies were conducted in Uganda [48,49], Ghana [50,51], Burundi and Rwanda [52], Thailand [53], International Journal of Reproductive Medicine India [54], and Kenya [55]. From the remaining four studies, one was conducted in Addis Ababa, Ethiopia [56] and excluded because of the unreported outcome of interest.…”
Section: Search Resultsmentioning
confidence: 99%
“…Women can independently initiate contraceptive choices, while men are not always aware of the partner’s contraceptive method and may not be aware of all contraceptives used (e.g., their partners’ oral or hormonal contraceptive use). A study in Chiang Mai, a Northern province of Thailand [ 22 ], showed that the rate of contraceptive use in postpartum HIV-uninfected women was high (97.6 %) and most used modern contraceptive methods; males reported condom use only 7.7 % of the time [ 22 ]. In contrast, a study of HIV-infected women in Chiang Mai found that 87 % of their partners used condoms [ 17 , 23 25 ] and 18–56 % of the women used dual contraceptive methods; consistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of family planning with maternal and child health programs has emerged as an attractive option in recent years as part of the “continuum of care” framework [ 19 ]. The periods of pregnancy, delivery, and postpartum are considered opportune for counseling women on the adoption of modern family planning methods due to frequent encounters with the health system [ 3 , 20 , 21 ]. Integration is anticipated to provide multiple opportunities to streamline service delivery and improve care at favorable and critical times for maximizing women’s reproductive health and the health of their children.…”
mentioning
confidence: 99%